Corticospinal vs Rubrospinal Revisited: An Evolutionary Perspective for Sensorimotor Integration - Olivares-Moreno, Rafael; Rodriguez-Moreno, Paola; Lopez-Virgen, Veronica; Macías, Martín; Altamira-Camacho, Moisés; Rojas-Piloni, Gerardo (Frontiers in Neuroscience, 2021)
The knowledge about how different subsystems participate and interplay in sensorimotor control is fundamental to understand motor deficits associated with CNS injury and movement recovery. The role of corticospinal and rubrospinal projections in motor control has been extensively studied and compared, and it is clear that both systems are important for skilled movement. However, during phylogeny, the emerging cerebral cortex took a higher hierarchical role controlling rubro-cerebellar circuits. Here, we present anatomical, neurophysiological and behavioral evidence suggesting that both systems modulate complex segmental neuronal networks in a parallel way, which is important for sensorimotor integration at spinal cord level. We also highlight that, although specializations exist, both systems could be complementary and potentially subserve motor recovery associated with CNS damage.